How Far Has Audit Quality been Researched? - Muhammad Taqi (SMART Insight, 2020)
The audit has a significant function as an instrument of external corporate governance, and audit quality. Affect audit governance. The overall objective of the audit is to obtain reasonable assurance that the financial statements do not contain substantial misstatements due to fraud or error, to issue an audit report following auditing standards. This study aims to determine the development map of audit quality research that is indexed by Scopus and other reputable journals with the keyword